1923 S.C. Acts 221, no. 148, § 19 (¶ 3) - (:unkn) unknown (My University, 1923)
Prohibited the selling or giving to a minor a pistol or pistol cartridge, brass knucks, Bowie knife, dirk, loaded cane or slingshot. Also prohibited a parent from giving such a weapon to their child under 12 years old. Punishable by fine up to $50 or imprisonment up to 30 days.
Keywords: TRANSFER - MINORS